2020
DOI: 10.3389/fphys.2020.587215
|View full text |Cite
|
Sign up to set email alerts
|

Poor Walking Speed Is Associated With Higher Segment-Specific Arterial Stiffness in Older Adult Japanese Community Dwellers: A Cross-Sectional Study

Abstract: Walking speed as one index of gait ability is an important component of physical fitness among older adults. Walking speed-arterial stiffness relationships have been studied, but whether poor walking speed is associated with higher segment-specific arterial stiffness in older adults is unclear. We thus aimed to examine the relationship between walking speed and segmental arterial stiffness among older community dwellers. This study was a cross-sectional study of 492 older Japanese community dwellers (age range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 59 publications
(123 reference statements)
0
12
0
Order By: Relevance
“…However, ankle diastolic and mean BPs were decreased by EMS. Furthermore, CAVI is generally an indicator of systemic PWV (i.e., haPWV) after adjusting for BP, and haPWV comprises hbPWV and baPWV elements ( Kume et al, 2020 ; Ogawa et al, 2020 ). In the present study, no significant changes in hbPWV were observed, reflecting arterial stiffness of the upper limbs from the aorta to the brachium ( Sugawara et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, ankle diastolic and mean BPs were decreased by EMS. Furthermore, CAVI is generally an indicator of systemic PWV (i.e., haPWV) after adjusting for BP, and haPWV comprises hbPWV and baPWV elements ( Kume et al, 2020 ; Ogawa et al, 2020 ). In the present study, no significant changes in hbPWV were observed, reflecting arterial stiffness of the upper limbs from the aorta to the brachium ( Sugawara et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…BP and PWVs were measured with the patient supine using a VS-1500AE/AN semi-automated device (Fukuda Denshi, Tokyo, Japan) as assessment parameters for each trial before and 5 and 30 min after each trial ( Nishiwaki et al, 2017 ; Nishiwaki et al, 2019 ; Nishiwaki et al, 2020 ; Ogawa et al, 2020 ). Cuffs to measure BP and PWV were wrapped around both upper arms and the ankles, then CAVI, heart-ankle PWV (haPWV), brachial-ankle PWV (baPWV), and heart-brachial PWV (hbPWV) were used as indices of arterial stiffness.…”
Section: Methodsmentioning
confidence: 99%
“…After resting for >15 min, we measured PWV, BP, and heart rate (HR) with the participant supine using a semi-automated device (VS-1500AE/AN; Fukuda Denshi, Tokyo, Japan), as previously described 18,19) . According to previous studies [20][21][22] , CAVI, heart-ankle PWV (haPWV), heart-brachial PWV (hbPWV), and brachial-ankle PWV (baPWV) were calculated as indicators of arterial stiffness. Intraobserver CVs for CAVI, haPWV, hbPWV, and baPWV determined in the laboratory on two separate days were 3.6 ± 1.9%, 2.6 ± 2.6%, 4.2 ± 3.4%, and 2.7 ± 1.5%, respectively 18,19,23) .…”
Section: Participants and Methodsmentioning
confidence: 99%
“…In light of this importance, the associations of several physical fitness surrogate measures, such as grip strength, walking speed, and balance tests with arterial stiffness, have been examined. [15][16][17] However, these studies were limited by the small number of participants. [15][16][17] In addition, some studies have reported inconsistent results.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] However, these studies were limited by the small number of participants. [15][16][17] In addition, some studies have reported inconsistent results. [15,18,19] Therefore, this study aimed to investigate the relationship between various physical fitness parameters and systemic arterial stiffness in older adults.…”
Section: Introductionmentioning
confidence: 99%